984. Diagnostic Utility of Bronchoalveolar Lavage Pneumocystis jirovecii DNA Polymerase Chain Reaction Assay in Patients with Hematological Malignancies and Hematopoietic Cell Transplantation. (4th December 2021) - Nanayakkara, Deepa; Tegtmeier, Bernard; Ross, Justine Abella; Dickter, Jana; Puing, Alfredo; Ho, Stephanie; Taplitz, Randy; Dadwal, Sanjeet
Abstract: Background: Pneumocystis jirovecii, an ubiquitous fungus, can lead to opportunistic pneumonia (PJP) in patients with hematological malignancies (HM) and hematopoietic cell transplantation (HCT) with mild to severe presentation. Unlike patients with HIV, diagnosis of PJP pneumonia is often challenging in patients with HM/HCT possibly related to lower fungal burden versus atypical presentation. The gold standard for diagnosis of PJP from bronchoalveolar lavage fluid (BALF) is cytology, followed by direct fluorescent antigen (DFA), however, in the context of lower fungal burden, quantitative polymerase chain reaction (PCR) is increasingly used. PCR DNA load cut-off for diagnosis of PJP is not established. The objective of this study is to assess the correlation between three tests (cytology, DFA and PCR) and diagnosis of PJP (colonization, possible, probable or proven infection). Methods: In this retrospective study at City of Hope, HM/HCT patients with BALF performed to investigate pneumonia who tested positive for any of the 3 tests were included. The study period is from July 2014 to July 2020. All patients had a clinical and radiographic diagnosis of pneumonia. Results: Eighty-five patients were identified to have at least one positive diagnostic test for PJP. Twenty (23.5%) patients had a PCR with less than 84 copies/mL, and colonization was suspected in these patients. Of the remaining 65 patients, 46 had all 3 tests done. Twenty seven (58.7%) patients only had positive PCR ranging from 106 to 588, 000 copies/mL with negative DFA and cytology. Twelve (26.1%) patients had either DFA or cytology positive with a positive PCR, and in 6 patients (13%) all 3 tests were positive. All of these 18 patients had clinical presentation and radiographic findings consistent with PJP. Quantitative or qualitative serum beta-D-glucan (BDG) level was available in 28 patients and 17 had a positive test with a level >80 pg/ml. Conclusion: PJP PCR is a very sensitive test that can lead to early detection of PJP pneumonia in HM/HCT with lower sensitivity of DFA/cytology unless the fungal burden is high. However, the optimal cut off PCR value associated with disease needs to be clinically validated in our patient population and a concurrent serum BDG level can increase diagnostic yield. Disclosures: All Authors : No reported disclosures